2008
DOI: 10.1007/s11055-008-9076-4
|View full text |Cite
|
Sign up to set email alerts
|

Delta sleep-inducing peptide and Deltaran: Potential approaches to antistress protection

Abstract: The aims of the present work were to perform a comparative study of the effects of delta sleep-inducing peptide and Deltaran on neurons in emotiogenic brain structures and to address the question of whether it is possible to prevent or decrease the negative influences of stress loads on the severity of subsequent cerebral ischemia in rats, using glycine with delta sleep-inducing peptide combined in the neuroprotective formulation Deltaran. The results showed that Deltaran and delta sleep-inducing peptide had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A reduced volume of infarction in ischemic tissues may be due to the ability of DSIP (and possibly its analogs) to increase the blood flow in the tissues [4]. Increased cerebral blood flow and a decrease in mortality after cerebral ischemia were demonstrated in the study by Koplik et al [18], in which male Wistar rats were subjected to global cerebral ischemia caused by bilateral occlusion of the carotid arteries, and preventively received DSIP at a dose of 10 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced volume of infarction in ischemic tissues may be due to the ability of DSIP (and possibly its analogs) to increase the blood flow in the tissues [4]. Increased cerebral blood flow and a decrease in mortality after cerebral ischemia were demonstrated in the study by Koplik et al [18], in which male Wistar rats were subjected to global cerebral ischemia caused by bilateral occlusion of the carotid arteries, and preventively received DSIP at a dose of 10 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional structural changes or coupling are necessary to ensure intestinal membrane permeability for DSIP [52]. A successful attempt in DSIP application was the creation of Deltaran in which DSIP is combined with glycine for intranasal administration of an aqueous solution [53]. Subsequent studies demonstrated geroprotective, anticarcinogenic and neuroprotective effects of DSIP and Deltaran [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the treatment of Wistar rats with DSIP several hours prior to global brain ischemia improved locomotor functions and reduced lethality [ 23 ]. DSIP reduced neuronal activity and improved blood supply of the brain of stressed animals subjected to brain ischemia [ 24 ]. There are several reports suggesting that DSIP reduces stress-induced overproduction of free radicals in CNS and prevents neuronal death [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%